The National Heroes in the Indonesian History Curriculum - Pramono, Suwito Eko; Ahmad, Tsabit Azinar; Utama, Nanda Julian; Atno, Atno; Kurniawan, Ganda Febri; Nurpratiwi, Hany; Plangsorn, Boonrat (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: Indonesia has plenty of national heroes. In education, they have the potential as a medium for transmitting values and character education. From 1959 to 2023, the president awarded the title of hero to 206 people. This number will continue to increase every year. However, the contribution of learning about national heroes has not been studied in depth. Therefore, this paper aims to analyze how national heroes' mapping in history class and the heroes' position in the Indonesian History curriculum. This paper also examines the internalization of heroic values and obstacles encountered in historical learning. Data was collected on policies related to hero titles, curriculum documents, history textbooks, and learning cases about national heroes in Semarang City. The results showed that historical learning in the Indonesian curriculum accommodated the teaching of heroes. Some material addressed the role of the hero explicitly. However, not all heroes were conveyed in the lesson. Overproduction of heroes was counterproductive to students' recognition of the value of heroism. On the one hand, the role of local heroes had not been optimally reviewed. As a result, history learning was stuck on the term